The transition rates for 232Th using the two component particle-hole state density with different corrections - Jasim, Mahdi H. (Iraqi Journal of Physics, 2012)
The particle-hole state densities have been calculated for 232Th inthe case of incident neutron with  ,  1 Z Z T T T T and   2 Z T T .The finite well depth, surface effect, isospin and Pauli correction areconsidered in the calculation of the state densities and then thetransition rates. The isospin correction function ( ) iso f has beenexamined for different exciton configurations and at differentexcitation energies up to 100 MeV. The present results are indicatedthat the included corrections have more affected on transition ratesbehavior for        , , and    above 30MeV excitation energy